2013
DOI: 10.1002/sm2.18
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Continuous Positive Airway Pressure Treatment on Sexuality in Female Patients with Obstructive Sleep Apnea

Abstract: IntroductionResults from a previous study showed that sexuality was negatively affected in females with untreated obstructive sleep apnea (OSA). Data are sparse on the long-term effects of nocturnal continuous positive airway pressure (CPAP) treatment on sexual difficulties and sexual distress in female patients with OSA.AimThe aim of the present study was to investigate the effects after 1 year of CPAP treatment on sexual difficulties, sexual distress, and manifest sexual dysfunction in female patients with O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In a prospective study, Jara et al [13] reported that, in severe OSA patients, CPAP treatment was associated with improved sexual quality of life, but not in men. Similarly, Peterson et al [14] also reported that, after 1 year of CPAP treatment, female patients with OSA reported reduced sexual dysfunction. We determined a significant negative correlation between the severity of OSAS and both sexual health and quality of life scores and all scores were improved after 6 months of effective CPAP treatment.…”
Section: Discussionmentioning
confidence: 85%
“…In a prospective study, Jara et al [13] reported that, in severe OSA patients, CPAP treatment was associated with improved sexual quality of life, but not in men. Similarly, Peterson et al [14] also reported that, after 1 year of CPAP treatment, female patients with OSA reported reduced sexual dysfunction. We determined a significant negative correlation between the severity of OSAS and both sexual health and quality of life scores and all scores were improved after 6 months of effective CPAP treatment.…”
Section: Discussionmentioning
confidence: 85%
“…Petersen et al. [53] showed that OSA patients with sexual dysfunction treated with CPAP had significant improvement as compared with the controls. Conceivably, the beneficial effect of CPAP on the male sexual function with OSA could also be extrapolated to women.…”
Section: Discussionmentioning
confidence: 99%
“…Improving lifestyle can improve nocturnal hypoxia, which can allow glucose homeostasis [96]. It has been reported that female patients with OSA have seen improvements in sexual dysfunction after a year of CPAP treatment [97]. Post menopause stages and waist size are correlated with the severity of OSA.…”
Section: Femalesmentioning
confidence: 99%